Pengaruh Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor terhadap Kepuasan Masyarakat di Kantor Bersama SAMSAT Ketintang Surabaya Selatan - Perkasa, Elang Bahar; Tukiman, Tukiman (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the quality of service on the satisfaction of Motor Vehicle Taxpayers at the Ketintang Samsat Joint Office, South Surabaya. The methodology used in this research is of the quantitative variety, especially the quantitative descriptive type. The quantitative method as explained by Sugiyono (2015) is known as the positivistic method because of its foundation in the philosophy of positivism; However, this method is a scientific method because it is combined with scientific principles. Samsat is a single, one-stop administrative system. The Samsat Joint Office is one of the public service places, handling the payment of Motor Vehicle Tax (PKB), Motor Vehicle Title Fee (BBNKB) and also Mandatory Road Traffic Accident Fund donations (SWDKLLJ). Based on data obtained by researchers directly from the research object, the South Surabaya Samsat Joint Office (Samsat B) which is located on Jalan Ketintang Sraten was inaugurated for use by the East Java Provincial Secretariat on April 29 2000, the South Surabaya Samsat building was built on a land area of 5,945 m2 and a building covering an area of 5,400 m2 consisting of two floors, each measuring 378 m2, the status of this land is owned by the East Java Provincial Government with Certificate Number: 35 LAK 245248 dated 01 October 1997. Based on the discussion and conclusions that can be drawn, namely the Samsat Office in Kentintang Selatan, Surabaya, still has some room for improvement in terms of responsiveness in providing services to customers, as well as extensive employee knowledge and insight, as well as skills in carrying out their duties, politeness towards patients, and other aspects of guarantees or guarantees, need to be improved . It is hoped that it can be used as evaluation material to improve service quality, especially at the Surabaya City Samsat office.